(untitled) (The International Research Journal of Management Science, 2024)
Purpose- The primary purpose of this study is to examine the relationship between ethical leadership and innovative behavior of employees in Nepalese commercial banks with the mediating role of organizational support. Design/Methodology/Approach- To examine the relationship between ethical leadership and innovative behavior, with organizational support as a mediator, a descriptive and causal research design was employed. Data were collected from a sample of 287 employees at various capacity levels within Nepalese commercial banks, using a convenience sampling technique. Findings- This study reveals that ethical leadership significantly fosters innovative behavior among employees in Nepalese commercial banks, with organizational support serving as a key mediating factor. Strong organizational support amplifies this relationship by offering essential resources, encouragement, and a secure environment that nurtures creativity and innovation. Implications- The findings of the study indicate that prioritizing ethical leadership training and strengthening organizational support systems can substantially boost employee innovative behaviour. This, in turn, contributes to enhance organizational performance and strengthens competitive advantages of the business. Originality/Value- This study provides new insights into the impact of ethical leadership and organizational support system on innovative behavior. Further it supports for fostering a culture of innovation, which is critical for enhancing competitiveness in the banking sector.